Characterization of tetracycline and erythromycin resistance determinants in Treponema denticola. - Roberts, M C (1996)
Treponema denticola isolates were evaluated for the presence of known tetracycline and erythromycin resistance determinants by Southern blot hybridization of whole-cell DNA and PCR assays. We examined all isolates available, which included 12 clinical and 4 American Type Culture Collection isolates. Two isolates carried the Tet B determinant, five isolates carried both the Tet B and Erm F determinants, seven isolates carried the Erm F determinant, and two did not carry any of the Tet or Erm determinants tested. Both the Tet B and Erm F determinants appeared to be associated with the chromosome. Neither of the two T. denticola donors tested could transfer the Tet B determinant, but three of four T. denticola tested transferred the Erm F determinant to an Enterococcus faecalis recipient. This extends the host range of both the tetB and ermF genes into the genus Treponema.